PERANCANGAN SISTEM INFORMASI REGISTRASI DAN LAPORAN PENDERITA HIV DAN AIDS BERBASISVB NET DAN ACCESS 2010 DI KOMISI PENANGGULANGAN AIDS (KPA) KAB. KARAWANG - bayu rohman; AHMAD ANAS; aminuddin (STMIK Pamitran, 2025)
The scientific work Outlines the system of registration information and reports of HIV and AIDS sufferers. The information system USES the waterfall method aimed at facilitation for a computerized worksystem in the form of a software application using a visual basic net. With a computerized program, the data processing will be more effective and minimize errors, so that the archives can be neatly arranged and when you want to know information can be faster and efficient. The solution provided to improve the current system in the Commission for the Prevention of HIV and AIDS Kab Karawang is to improve the old system with a new system that is more effective and efficient in producing information for the needs of agencies, especially in KPA Kab Karawang.